Kelley. The story of an FBI director - Kelly, C. M., Kirkp, J. (New York McMeelandParker, 1987)
This is the inside story of law inforcement in the United States from 1940 to 1978 as told by a man who witnessed some of the most turbulent events in modern American history. From FBI agent to chief of police to director of the FBI, Kelleys integrity and honesty stand out against the backdrop of organizations and administrations marked by secretive and covert activities.
Keywords: Biography